2020
DOI: 10.3889/oamjms.2020.4739
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Oxytocin and Marmet Massage on Increased Prolactin Hormone for Smooth Breastfeeding in Postpartum Mothers in Langsa City Health Office, Indonesia

Abstract: BACKGROUND: One of the causes of the disruption to the achievement of exclusive breastfeeding is the decrease in milk production experienced by nursing mothers. It is believed that the prolactin hormone and the mother’s perception of breast milk are inadequate. One effort to increase the prolactin hormone is by massaging techniques. This technique has been used by various people in the world for both medical treatment and health care. AIM: The purpose of this study was to analyze the differences in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This implies that being emotionally stable, in terms of being happy and comfortable, will positively influence the mother's ability to exclusively BF. On the other hand, being emotionally upset, stressed, and fatigued will negatively affect the exclusive BF through the effects of prolactin and oxytocin hormones , this was supported as well by Emilda [15] and Mensah. [16] Therefore, women will have inadequate milk production and this is the reason for early supplementation.…”
Section: Early Days After Deliverymentioning
confidence: 87%
See 1 more Smart Citation
“…This implies that being emotionally stable, in terms of being happy and comfortable, will positively influence the mother's ability to exclusively BF. On the other hand, being emotionally upset, stressed, and fatigued will negatively affect the exclusive BF through the effects of prolactin and oxytocin hormones , this was supported as well by Emilda [15] and Mensah. [16] Therefore, women will have inadequate milk production and this is the reason for early supplementation.…”
Section: Early Days After Deliverymentioning
confidence: 87%
“…This study showed that in the early days after delivery, mothers have negative emotions toward initiation of BF due to several factors as stated by mothers. These factors include perceptions regarding inadequacy in the amount of milk, [13,15,16] physical discomfort or fatigue, and poor knowledge about BF positioning and attachment techniques. In terms of the amount of milk, mothers stated that they believed their milk is not enough; therefore they tend to introduce formula milk.…”
Section: Early Days After Deliverymentioning
confidence: 99%
“…Numerous individuals around the globe have utilized this method for both treatment and health care. Emilda & Juliastuti (2020) in Langsa City, Aceh, Indonesia, she analyzed differences in the efficacy of Oxytocin and Marble Massage on Prolactin Hormone levels for the ease of lactation in postpartum mothers at the Langsa City Health Center. The highest level of prolactin hormone in the massage method was 1178.0 g/ml, and the maximum level of prolactin hormone was 357.9 g/ml.…”
Section: Differential Effects Of Oxytocin and Marble Massage On The E...mentioning
confidence: 99%
“…Without exclusive breastfeeding, there is a rise in the reliance on formula milk. Factors like insufficient breast milk production post-birth, challenges in baby latching, problematic maternal nipples, maternal employment, and aggressive marketing of formula milk can hinder breastfeeding (Emilda & Juliastuti, 2020). Observations in real-life scenarios indicate that many mothers face challenges with low breast milk production in the initial days after delivery.…”
Section: Introductionmentioning
confidence: 99%